Upaya Peningkatan keamanan Pangan pada Pelaku Usaha Pangan Segar Asal Tumbuhan (PSAT) di Kota Mataram - M. Sarjan; Aluh Nikmatullah; Hery Haryanto; Ruth Stella Thei; Amrul Jihadi (Pascasarjana Universitas Mataram, 2022)
As a result of the outbreak of the COVID-19 pandemic which was followed by the imposition of large-scale social restrictions (PSBB) in Indonesia, it has encouraged people to adopt healthier lifestyles and at the same time carry out a number of environmentally friendly activities. Therefore, it is necessary to make efforts to improve understanding and practice of cultivation as well as guarantee the quality of the food produced, among others by carrying out socialization